A 56 Years Old Female with Uncontrolled Diabetes Mellitus Type II, Pneumonia, and Suspect With Lung Abscess: a Case Report - Fahreza Fahreza; Diana Novita; Sri Meutia (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background:Diabetes mellitus is a group of metabolic diseases with characteristic hyperglycemia. Proper management of DM patients is essential, and this is useful for controlling appropriate blood glucose levels. If blood glucose levels are uncontrolled, this lead to other complications in other organs, like interference with the immune system. Disruption of the immune system causes the risk of infectious diseases, such as pneumonia and lung abscess.Case Presentation:We report a female patient with a history of type 2 diabetes mellitus, complaining of dyspnea, cough with sputum, high fever, and headache. On chest examination showed left chest movement in the right lung, increased stem fremitus in all right lung fields, dullness in the right upper lung field, and amphoric sound, coarse and wet crackles heard in the right upper lung.  Several supporting examinations, including laboratory and radiological examinations were carried out.Conclusion: The patient was diagnosed with uncontrolled type 2 diabetes mellitus, pneumonia, and a suspected lung abscess. The patient was given several treatments and showed clinical improvement on the fifth day of treatment.